Understanding irritability through the lens of self-regulatory control processes in children and adolescents: a systematic review - Urben, Sébastien; Ochoa Williams, Ana; Ben Jemia, Cécile; Rosselet Amoussou, Joëlle; Machado Lazaro, Sara; Giovannini, Julia; Abi Kheir, Marion; Kaess, Michael; Plessen, Kerstin Jessica; Mürner-Lavanchy, Ines M. (European child & adolescent psychiatry, 2025)
Among youths, pathological irritability is highly prevalent and severely disabling. As a frequent symptom, it often leads to referrals to child and adolescent mental health services. Self-regulatory control (SRC) processes are a set of socio-psycho-physiological processes that allow individuals to adapt to their ever-changing environments. This conceptual framework may enhance the current understanding of the cognitive, emotional, behavioural and social dysregulations underlying irritability. The present systematic review (PROSPERO registration: #CRD42022370390) aims to synthesize existing studies that examine irritability through the lens of SRC processes among youths (< 18 years of age). We conducted a comprehensive literature search among six bibliographic databases: Embase.com, Medline ALL Ovid, APA PsycInfo Ovid, Web of Science Core Collection, the Cochrane Database of Systematic Reviews Wiley and ProQuest Dissertations & Theses A&I. Additional searches were performed using citation tracing strategies. The retrieved reports totalled 2612, of which we included 82 (i.e., articles) from 74 studies. More than 85% of reports were published during the last 6 years, highlighting the topicality of this work. The studies sampled n = 26,764 participants (n = 12,384 girls and n = 12,905 boys, n = 1475 no information) with an average age of 8.08 years (SD = 5.26). The included reports suggest that irritability has an association with lower effortful control, lower cognitive control and delay intolerance. Further, evidence indicates both cross-sectional and longitudinal associations between irritability and a lack of regulation skills for positive and negative emotions, particularly anger. Physiological regulation seems to moderate the association between irritability and psychopathology. Finally, the mutual influence between a child’s irritability and parenting practice has been established in several studies. This review uses the lens of SRC to illustrate the current understanding of irritability in psychopathology, discusses important gaps in the literature, and highlights new avenues for further research.
Online veröffentlicht: 8. Oktober 2024
Gesehen am 08.04.2025